A book club to die for - St. James, Dorothy (St. James, Dorothy. Beloved bookroom mysteries, 2022)
"When a member of an exclusive book club is poisoned, spunky librarian Trudell Beckett must sort fact from fiction to solve the murder. The Cypress Arete Society is the town's oldest and most exclusive book club. When Trudell Beckett, the town's spunky assistant librarian, is invited to speak to the club about the library, its modernization, and her efforts to bring printed books to the reading public, Trudell's friend Flossie invites herself along. Flossie has been on the book club's waiting list for five years, and she's determined to find out why she's never received an invitation to join. When Tru and Flossie arrive early for the book club, they're shocked to find the club leader, Rebecca White, dead in the kitchen. The main suspect: Detective Jace Bailey's mother, the host for the evening. With Jace removed from the case due to the conflict of interest, Trudell must help him investigate and prove his mother's innocence in a case where nothing is as it seems"--